Endomorfismos subrejetores de grupos e anéis de matrizes triangulares superiores de ordem infinita - Cesar Postingel Ramos (2018)
The aim of this work is to describe the onto endomorphisms of the ring of triangular matrices of order |N| × |N| over a field with at least three elements. To do so, we first describe the onto endomorphisms of the group of the invertible upper triangular matrices of the same order